If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(3x + 5) + 5x = 5(2x + -3) Reorder the terms: 4(5 + 3x) + 5x = 5(2x + -3) (5 * 4 + 3x * 4) + 5x = 5(2x + -3) (20 + 12x) + 5x = 5(2x + -3) Combine like terms: 12x + 5x = 17x 20 + 17x = 5(2x + -3) Reorder the terms: 20 + 17x = 5(-3 + 2x) 20 + 17x = (-3 * 5 + 2x * 5) 20 + 17x = (-15 + 10x) Solving 20 + 17x = -15 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 20 + 17x + -10x = -15 + 10x + -10x Combine like terms: 17x + -10x = 7x 20 + 7x = -15 + 10x + -10x Combine like terms: 10x + -10x = 0 20 + 7x = -15 + 0 20 + 7x = -15 Add '-20' to each side of the equation. 20 + -20 + 7x = -15 + -20 Combine like terms: 20 + -20 = 0 0 + 7x = -15 + -20 7x = -15 + -20 Combine like terms: -15 + -20 = -35 7x = -35 Divide each side by '7'. x = -5 Simplifying x = -5
| 7-8x^2=0 | | 5.6-x=0.5 | | 4w-3x-y+3w+15x-4y= | | -12.5x^3-50x^2=0 | | -x^3+5x^2-42x+234=0 | | 4.5-3.9x=20.1 | | 3b+15=9b+3 | | 4z-(7+3z)=2 | | 7b-4=3b+16 | | 8x-2y+11w-3y-4w+4x= | | 3(x+3)-2(2x-3)=0 | | (5x+4)-(2x+4)= | | 6x+5+2x-1=20 | | (3sinx-2)(2cosx+1)=0 | | 37(8x-23)=37 | | F(x)=60+10 | | 5+5x=7x+5 | | 3b+2=b+10 | | 4w+8y+3x+9x-13y+4w= | | 2x-2(x+11)=5x | | y=3x^2+16x-8 | | 4w+9x+11y+3w+3x-6y= | | 5p+7=4p+3 | | 5h-4=-16 | | x+3(x-1)=4 | | 9+2.71t=-4.8t-6 | | -x^2-2x-8=0 | | 24-x=18 | | -x^2-7x+22=0 | | M^2+7M=4 | | 2(x+3y-1)=y | | 5(x-y)+2y=-26 |